Answer:
x = -2
Step-by-step explanation:
Since we know they will have the same output, we can set them equal to each other in an equation. We'll use x to represent the input.
3x + 6 = 8(x + 2) (Given)
3x + 6 = 8x + 16 (Distributed the 8)
6 = 5x + 16 (Subtracted 3x on both sides)
-10 = 5x (Subtracted 16 on both sides)
-2 = x (Divided 5 on both sides)
y=-2x+7
Step-by-step explanation:
line segment xy has endpoints x(5 7) and y(-3 3)
for the equation of the perpendicular bisector of line segment xy
slope of line segment xy = 7-3 / 5+3
= 4/8
=1/2
so slope of perpendicular bisector is -2
as m1m2= -1 or m1= -1/m2
As perpendicular bisector goes through midpoint of xy , let's find midpoint of xy
midpoint(x,y) = (5-3 / 2 , 7+3 / 2)
=(2/2, 10/2)
=(1,5)
find the equation of line(perpendicular bisector) passing through (1,5) and the slope -2
y-5 = -2(x-1)
y-5 =-2x+2
y=-2x+7
Answer: x = 3
Step-by-step explanation:
2(7x - 6) = 30
14x - 12 = 30
+ 12 +12
14x = 42
/14 /14
x = 3